Internal and external cooling methods and their effect on body temperature, thermal perception and dexterity. - Matthew J Maley; Geoffrey M Minett; Aaron J E Bach; Stephanie A Zietek; Kelly L Stewart; Ian B Stewart (PLoS ONE, 2018)
The present study aimed to compare a range of cooling methods possibly utilised by occupational workers, focusing on their effect on body temperature, perception and manual dexterity.Ten male participants completed eight trials involving 30 min of seated rest followed by 30 min of cooling or control of no cooling (CON) (34°C, 58% relative humidity). The cooling methods utilised were: ice cooling vest (CV0), phase change cooling vest melting at 14°C (CV14), evaporative cooling vest (CVEV), arm immersion in 10°C water (AI), portable water-perfused suit (WPS), heliox inhalation (HE) and ice slushy ingestion (SL). Immediately before and after cooling, participants were assessed for fine (Purdue pegboard task) and gross (grip and pinch strength) manual dexterity. Rectal and skin temperature, as well as thermal sensation and comfort, were monitored throughout.Compared with CON, SL was the only method to reduce rectal temperature (P = 0.012). All externally applied cooling methods reduced skin temperature (P<0.05), though CV0 resulted in the lowest skin temperature versus other cooling methods. Participants felt cooler with CV0, CV14, WPS, AI and SL (P<0.05). AI significantly impaired Purdue pegboard performance (P = 0.001), but did not affect grip or pinch strength (P>0.05).The present study observed that ice ingestion or ice applied to the skin produced the greatest effect on rectal and skin temperature, respectively. AI should not be utilised if workers require subsequent fine manual dexterity. These results will help inform future studies investigating appropriate pre-cooling methods for the occupational worker.